2002
DOI: 10.1074/jbc.m109479200
|View full text |Cite
|
Sign up to set email alerts
|

Role of Trehalose Phosphate Synthase in Anoxia Tolerance and Development in Drosophila melanogaster

Abstract: Recent studies have shown that trehalose plays a protective role in yeast in a variety of stresses, including heat, freezing and thawing, dehydration, hyperosmotic shock, and oxidant injury. Because (a) heat shock and anoxia share mechanisms that allow organisms to survive, (b) Drosophila melanogaster is tolerant to anoxia, and (c) trehalose is present in flies and is metabolically active, we asked whether trehalose can protect against anoxic stress. Here we report on a new role of trehalose in anoxia resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
138
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 24 publications
6
138
0
Order By: Relevance
“…This central role of T6P may be more widely conserved than previously imagined. Beyond yeasts and plants, it could well be conserved in insects: Drosophila mutated in the TPS has recently been shown to be embryo lethal (48). There exists a particular pressing need to find the site and details of the T6P interaction in all these organisms.…”
Section: T6p Levels Determine the Accumulation Of Respiratory Intermementioning
confidence: 99%
“…This central role of T6P may be more widely conserved than previously imagined. Beyond yeasts and plants, it could well be conserved in insects: Drosophila mutated in the TPS has recently been shown to be embryo lethal (48). There exists a particular pressing need to find the site and details of the T6P interaction in all these organisms.…”
Section: T6p Levels Determine the Accumulation Of Respiratory Intermementioning
confidence: 99%
“…Even in so-called "normal" organisms, trehalose synthesis is elevated under stress conditions (most recently reviewed in Ref. 1), including dehydration, stationary phase culture, salt-stress (5), heat-shock (2), high pressure (6), extreme cold (7), exposure to oxygen radicals (8,9), and anoxia (10).…”
mentioning
confidence: 99%
“…Like Actn null mutants, null mutants of Tps1 typically die as first instars, 30 and once again, we observed that the RNAi phenotype was similar to that of a null mutation, but with reduced penetrance.…”
Section: Resultsmentioning
confidence: 73%